PERANCANGAN ZETA CONVERTER PADA PELACAKAN TITIK DAYA MAKSIMUM PHOTOVOLTAIC MENGGUNAKAN ALGORITMA MODIFIKASI HILL CLIMBING - Irwan Mahmudi; Jumiyatun Jumiyatun; Baso Mukhlis; Lukman Lukman (Foristek, 2021)
Electrical energy is a primary need at this time, which almost all human activities require electricity. The electrical energy we use today is a conversion from other energy, partly derived from fossil energy, which is energy that cannot be renewed and will run out if it is continuously explored and exploited. Solar energy is a renewable energy source that has the potential to be converted to electrical energy using solar panels or so-called photovoltaics. Photovoltaic has a drawback in its use, namely the output value is very dependent on environmental conditions. To maximize the power efficiency between the photovoltaic output and the power to be used by the load, a method is needed, namely Maximum Power Point Tracking (MPPT). In the application of this MPPT DC-DC Zeta converter is used with a hill climbing algorithm to achieve the value of the output voltage and current at maximum power. With this method, it is expected that MPPT control is reliable and easy to apply. In this study, the type of photovoltaic module used is the 60 Wp monocrystalline type with sampling data once an hour from 09.00 - 17.00 WITA, the tracking speed data obtained by the modified hill climbing algorithm is 0.142 seconds on average with an average efficiency of 99.969 %.